1989
DOI: 10.1002/1097-0142(19891201)64:11<2292::aid-cncr2820641119>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Grade adenocarcinoma of probable endolymphatic sac origin. A clinicopathologic study of 20 cases

Abstract: The clinical and histologic features of twenty cases of a type of papillary-cystic temporal bone neoplasm are reported. Ages of the patients ranged from 15 to 71 years. The tumors destroyed a large portion of the posterior temporal bone and included a prominent extension into the posterior cranial fossa. Patient histories indicated a slow growth rate of the lesions. Awareness of the parameters of this neoplasm, including the site of origin and probably histogenesis, may enable earlier diagnosis and more succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
206
0
18

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(231 citation statements)
references
References 13 publications
7
206
0
18
Order By: Relevance
“…El tratamiento quirúrgico, pese a la dificultad de extirpación completa (debido a su naturaleza agresiva local), se mantiene como el principal método de tratamiento 8 . Las indicaciones para el tratamiento quirúrgico se basan principalmente en la capacidad de curar completamente el tumor preservando la función cocleovestibular en lo posible.…”
Section: Discussionunclassified
“…El tratamiento quirúrgico, pese a la dificultad de extirpación completa (debido a su naturaleza agresiva local), se mantiene como el principal método de tratamiento 8 . Las indicaciones para el tratamiento quirúrgico se basan principalmente en la capacidad de curar completamente el tumor preservando la función cocleovestibular en lo posible.…”
Section: Discussionunclassified
“…Heffner (1) previously reported that this tumor should be called a low-grade adenocarcinoma, but now he considered that this tumor is not malignant in the sense that it is locally infiltrative without metastasizing (2). However, reports on the proliferation potential of ELST are very few.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The origin of this tumor is thought to be the endolymphatic sac (1,2). ELST histologically shows epithelial features, such as papillary architecture, glandular formation and a colloid-like structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations